Analisis Vegetasi Hutan Pamah di Pulau Batanta, Raja Ampat, Papua - Mirmanto, Edi (Perhimpunan Biologi Indonesia, 2009)
ABSTRACTVegetation Analysis of Lowland Forest in Batanta Island, Raja Ampat, Papua. A vegetationanalysis of Batanta lowland forest has been made by setting up 17 plots of each 30-m x 30-mdistributed in 3 study sites were Yenanas (5 plots), Yensawai (7 plots) and Wailebet (5 plots).All trees (dbh. eâ10 cm) within all of 17 plots were measured, and determined their positions,and identify their species. In total there were 171 tree species recorded within plots andbelonging to 108 genera and 40 families. Pometia pinnata was the most common speciesfollowed by Anthocephalus macrophyllus, Pangium edule, Toxotrophis illicifolius, andKoordersiodendron pinnatum. Almost all of common species such as Pometia pinnata,Anthocephalus macrophyllus, Celtis hidebrandii and Intsia bijuga were observed as theemergent and/or canopy trees. According to ordination analysis there were five communitytypes, AporusaâPometia, Antocephalus-Toxotrophis, Sterculia-Grewia, Ficus-Antocephalus,and Duabanga-Pterocymbium communities. However floristic compositions varied amongplot sites, which might be a characteristic of vegetation of Papua and the nearby small islands.Keywords: Vegetation, lowland forest, Raja Ampat, PapuaKata kunci: Vegetasi, hutan dataran rendah, Raja ampat, Papua